2017
DOI: 10.18203/2394-6040.ijcmph20174228
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of immunization services at immunization sessions under Ghatnandur PHC area in Beed district

Abstract: Background: It was realized that just providing vaccine to achieve targets without giving attention to quality of services doesn’t guarantee a reduction in disease morbidity & mortality. Operational challenges such as logistic supply and microplanning have to be taken into consideration There is also increasing need to ensure that providers stick to service delivery protocols to achieve better health outcomes. Therefore the Study was aimed to assess the immunization sessions. The objective of the study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…It was similar to the study conducted by Salunke et al . [ 24 ] in Beed district, they found that availability of logistics for vaccination sessions was more than 80% at all vaccination sessions but the major problem was that the information about side effects were not provided to people.…”
Section: Discussionmentioning
confidence: 99%
“…It was similar to the study conducted by Salunke et al . [ 24 ] in Beed district, they found that availability of logistics for vaccination sessions was more than 80% at all vaccination sessions but the major problem was that the information about side effects were not provided to people.…”
Section: Discussionmentioning
confidence: 99%